Low-sintering-shrinkage photocuring 3D printing ceramic slurry and preparation method thereof

Through acid spraying and reasonable mixing of nano alumina and silica, photocuring 3D printed ceramic slurry with high ceramic phase volume fraction is prepared, which solves the problem that traditional ceramic forming methods are difficult to produce large-size, complex-shaped ceramic components and high sintering shrinkage, and achieves high precision and high mechanical properties of ceramic components.

CN119774990APending Publication Date: 2025-04-08LANZHOU CITY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411994498.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional ceramic forming methods are difficult to produce large-size and complex-shaped ceramic components, and the photocured 3D printed ceramic slurry has a high sintering shrinkage rate during the sintering process, which affects the dimensional accuracy and mechanical properties of the product.

Method used

The nano-alumina powder was activated by spraying acid, and the alkaline alumina intermediate and nano-silica powder were reasonably mixed. Ultrasonic treatment of aqueous ammonia solution and ammonia discharge treatment were used to prepare a photocured 3D printed ceramic slurry with high volume fraction of the ceramic phase.

Benefits of technology

The sintering shrinkage rate of ceramic slurry is significantly reduced, less than or equal to 5.3%, and the dimensional accuracy, density and mechanical properties of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses low-sintering-shrinkage-rate photocuring 3D printing ceramic slurry and a preparation method thereof, and belongs to the field of 3D printing. The method comprises the following steps: performing acid spraying treatment on nano aluminum oxide powder, washing and drying to obtain a basic aluminum oxide intermediate, mixing the basic aluminum oxide intermediate with nano silicon dioxide powder, performing sealed ultrasonic treatment in an ammonia water solution, and performing ammonia discharge treatment to finally obtain the low-sintering-shrinkage photocuring 3D printing ceramic slurry. The method has the advantages of high component control precision, high process stability and high repeatability, and excellent sintering performance of the photocuring 3D printing ceramic slurry can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing, and in particular to a light-cured 3D printing ceramic slurry with low sintering shrinkage and a preparation method thereof. Background Art

[0002] Ceramic materials have the advantages of high temperature resistance, low thermal expansion coefficient, and high hardness, and are widely used in semiconductors, aerospace, biomedicine and other fields. Especially in modern engineering technology that pursues lightweight, high efficiency and adaptability to extreme environments, the application of ceramic materials is particularly important. However, traditional ceramic forming methods are difficult to produce large-sized and complex-shaped ceramic parts, which greatly limits the application potential of ceramic materials in a wider range of industrial fields.

[0003] In recent years, the rise of photocuring 3D printing technology has brought revolutionary breakthroughs to the ceramic manufacturing industry. Photocuring 3D printing technology has the advantages of high precision and flexible structural design, and is an emerging manufacturing technology for large and complex ceramic structures. One of the core issues of photocuring 3D printing is the optimization of the ceramic slurry formula. In order to ensure the good fluidity of the slurry during the 3D printing process and the uniform dispersion of ceramic particles, it is often necessary to add a large volume ratio of solvent (≥30%). These solvents will be removed during the subsequent sintering process, resulting in significant sintering shrinkage, which not only affects the dimensional accuracy of the final product, but may also cause internal stress concentration and reduce the mechanical properties and reliability of ceramic parts. Therefore, increasing the volume fraction of the ceramic phase in photocuring 3D printing ceramic slurry is a key technology to reduce its sintering shrinkage, improve 3D printing effects, and optimize the sintered structure and performance of ceramics. Summary of the invention

[0004] The present invention aims to solve the engineering problem of high sintering shrinkage of commonly used photocurable 3D printing ceramic slurry, and provides a photocurable 3D printing ceramic slurry with low sintering shrinkage and a preparation method thereof.

[0005] In order to achieve the above object, the present invention is implemented by adopting the following technical scheme: The present invention provides a method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage, comprising: The nano-alumina powder is treated by spraying acid, then washed and dried to obtain a basic alumina intermediate; The basic alumina intermediate is mixed with nano-silica powder to obtain a mixed powder, the mixed powder is placed in an ammonia solution and sealed for ultrasonic treatment, and finally an ammonia removal treatment is performed to obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0006] The average particle size of the nano alumina powder is 15-24 nanometers.

[0007] The acid spraying treatment is specifically: During the acid spraying process, argon gas with a temperature of 46-58°C and a velocity of 105-122 m / s is used as the exciting gas flow, 28-32% hydrochloric acid solution is used as the strong acid medium, and the dosage of the strong acid medium is 8-11 ml per gram of nano-alumina powder; The nano-alumina powder is sprayed with strong acid medium for the first time, and the strong acid primary waste liquid generated in the acid spraying process is further sprayed with strong acid for the second time on the nano-alumina powder. The amount of the strong acid primary waste liquid is 22-36 ml per gram of nano-alumina powder. The strong acid secondary waste liquid generated in the acid spraying process is directly introduced into 15-20% sodium hydroxide for dissolution and recovery.

[0008] The nano-alumina powder is subjected to acid spraying treatment, followed by washing and drying, and specifically: The washing process uses deionized water as a medium, washing 3 to 5 times, and the drying process is performed at a temperature of 60 to 75° C. for 35 to 45 minutes.

[0009] The mass ratio of the basic alumina intermediate to the nano-silicon dioxide powder is 67-75:25-33.

[0010] The average particle size of the nano silicon dioxide powder is 12 to 18 nanometers.

[0011] The basic alumina intermediate and the nano-silicon dioxide powder are mixed by grinding to obtain a mixed powder, specifically: During the grinding process, the spindle speed is 36 to 42 revolutions per minute, the pressure at the end of the grinding rod is 4500 to 5100 Pa, and the grinding time is 17 to 21 minutes.

[0012] The mixed powder is placed in an ammonia solution and sealed for ultrasonic treatment, specifically: The mixed powder is ultrasonically treated in a 19-23% ammonia solution, the amount of ammonia solution is 3-6 ml per gram of mixed powder, the ultrasonic frequency is 70-90 KHZ, the temperature is 52-60°C, and the ultrasonic treatment time is 30-36 minutes.

[0013] The ammonia removal treatment is specifically: The mixture after ultrasonic treatment was placed in a heating and stirring device, the temperature was controlled at 62-72° C., and stirring was continued for 70-80 minutes to remove ammonia from the mixture after ultrasonic treatment.

[0014] The present invention also provides a photocurable 3D printing ceramic slurry with low sintering shrinkage obtained by the above preparation method. The ceramic phase volume ratio of the prepared ceramic slurry is greater than or equal to 74%, the average particle size of the ceramic phase is less than or equal to 37 nanometers, the porosity of the photocurable 3D printing ceramic green body is less than or equal to 8%, and the green body sintering shrinkage is less than or equal to 5.3%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention firstly treats nano-alumina powder with acid, then washes and dries it to obtain a basic alumina intermediate, then mixes the basic alumina intermediate with nano-silica powder, then places it in an ammonia solution for sealed ultrasonic treatment, and finally performs ammonia removal treatment; wherein the acid spraying treatment of the alumina powder is used to activate the powder surface on the one hand, which is beneficial to the suspension of the powder in the solution and improves its uniform mixing characteristics in the solution, and on the other hand, the alumina is made into basic alumina to optimize its photocuring performance; the basic alumina intermediate is mixed with the nano-silica powder and then ultrasonically treated in ammonia water, on the one hand, silica gelation is completed without changing the basic alumina composition and structure, thereby increasing the ceramic phase ratio of the slurry, and on the other hand, the ceramic dual phases are synchronously mixed to improve the slurry preparation efficiency. This method has high component control accuracy, strong process stability and repeatability, and can achieve low sintering shrinkage performance of photocurable 3D printing ceramic slurry.

[0016] Furthermore, limiting the average particle size of the nano-alumina powder can provide better dispersibility and specific surface area, which is beneficial to increasing the volume fraction of the ceramic phase, while improving the fluidity and printing accuracy of the slurry. The alumina powder within the particle size range provided by the present invention can not only ensure good processing performance, but also effectively reduce shrinkage during the sintering process.

[0017] Furthermore, the acid spraying treatment conditions, including temperature, air flow velocity, acid medium concentration and dosage, etc., can effectively activate the surface of the alumina powder. At the same time, the recycling of waste liquid reduces environmental pollution and improves resource utilization.

[0018] Furthermore, impurities and residual acid on the powder surface can be completely removed through washing and drying conditions to ensure the purity and stability of the slurry. At the same time, the appropriate drying temperature can avoid powder agglomeration or structural changes that affect the final slurry properties.

[0019] Furthermore, a reasonable mass ratio of the basic alumina intermediate to the nano-silica powder can balance the properties of the two ceramic phases, ensuring a high ceramic phase volume fraction of the slurry, while improving the rheology and printing performance of the slurry through the addition of silica, while reducing the sintering shrinkage.

[0020] Furthermore, the particle size control of nano-silicon dioxide helps to evenly disperse it in the slurry, thereby improving the stability of the slurry and the printing accuracy.

[0021] Furthermore, the grinding conditions provided in the present invention can ensure the full mixing and uniform dispersion of the two powders, and avoid agglomeration and phase separation.

[0022] Furthermore, ultrasonic treatment in an ammonia solution helps to break up agglomerates. A suitable ammonia solution can promote silica silicification and improve the ceramic properties of the slurry. Appropriate ammonia removal treatment can remove residual ammonia in the slurry to avoid adverse effects on subsequent printing and sintering processes.

[0023] The ceramic phase volume ratio of the ceramic slurry prepared by the present invention is greater than or equal to 74%, the average particle size of the ceramic phase is less than or equal to 37 nanometers, the porosity of the photocurable 3D printed ceramic body is less than or equal to 8%, and the sintering shrinkage of the body is less than or equal to 5.3%. These excellent properties can improve the accuracy, density and mechanical properties of 3D printed ceramic parts, and provide strong support for the manufacture of high-performance ceramic parts. DETAILED DESCRIPTION

[0024] In the following examples, unless otherwise specified, all materials used can be obtained through common channels; and the test methods adopted are conventional methods in the art.

[0025] The present invention discloses a photocurable 3D printing ceramic slurry with low sintering shrinkage and a preparation method thereof, comprising the following steps: 1) Using argon gas at a temperature of 46-58° C. and a velocity of 105-122 meters per second as an exciting gas flow, and 28-32% hydrochloric acid solution as a strong acid medium, a nano-alumina powder with an average particle size of 15-24 nanometers is subjected to a first acid spraying, and the amount of the strong acid medium is 8-11 milliliters per gram of the nano-alumina powder. The strong acid primary waste liquid generated during the acid spraying process is further subjected to a second acid spraying on the nano-alumina powder, and the amount of the strong acid primary waste liquid is increased to 22-36 milliliters per gram of the nano-alumina powder. The strong acid secondary waste liquid generated during the acid spraying process is directly introduced into 15-20% sodium hydroxide for dissolution and recovery; the nano-alumina powder after the two acid spraying treatments is washed with deionized water for 3-5 times, and after washing, is dried in an environment at a temperature of 60-75° C. for 35-45 minutes to obtain a basic alumina intermediate; 2) Using automatic grinding technology, the basic alumina intermediate and 12-18 nanometer silica powder are mixed in a mass ratio of 67-75:25-33. During the grinding process, the spindle speed is 36-42 rpm, the pressure at the end of the grinding rod is 4500-5100 Pa, and the grinding time is 17-21 minutes; the ground mixed powder is then placed in a 19-23% ammonia solution for sealed ultrasonic treatment, the amount of ammonia solution is 3-6 ml per gram of mixed powder, the ultrasonic frequency is 70-90KHZ, the temperature is 52-60°C, and the ultrasonic treatment is carried out for 30-36 minutes; the ultrasonically treated mixture is placed in a heating and stirring device, the temperature is controlled at 62-72°C, and the stirring is continued for 70-80 minutes, and the ultrasonically treated mixture is subjected to ammonia removal treatment to finally obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0026] The properties of the photocurable 3D printing ceramic slurry prepared in the following examples are shown in Table 1.

[0027] Example 1 1) using argon gas at a temperature of 46° C. and a velocity of 105 m / s as an exciting gas flow and 28% hydrochloric acid solution as a strong acid medium to perform a first acid spray on a nano-alumina powder having an average particle size of 15 nm, wherein the amount of the strong acid medium used is 11 ml per gram of the nano-alumina powder, and the nano-alumina powder is further subjected to a second acid spray using the strong acid primary waste liquid generated during the acid spraying process, wherein the amount of the strong acid primary waste liquid used is increased to 22 ml per gram of the nano-alumina powder, and the strong acid secondary waste liquid generated during the acid spraying process is directly introduced into 15% sodium hydroxide for dissolution and recovery; washing the nano-alumina powder after the two acid spraying treatments with deionized water for 3 times, and drying the nano-alumina powder at a temperature of 60° C. for 35 minutes after washing to obtain a basic alumina intermediate; 2) Using automatic grinding technology, the basic alumina intermediate and 12 nanometer silica powder were mixed in a mass ratio of 67:33. During the grinding process, the spindle speed was 36 rpm, the pressure at the end of the grinding rod was 4500 Pa, and the grinding time was 17 minutes. The ground mixed powder was then placed in a 19% ammonia solution and sealed for ultrasonic treatment. The amount of ammonia solution was 3 ml per gram of mixed powder, the ultrasonic frequency was 70KHZ, the temperature was 52°C, and the ultrasonic treatment was carried out for 30 minutes. The ultrasonically treated mixture was placed in a heating and stirring device, the temperature was controlled at 62°C, and stirring was continued for 70 minutes. The ultrasonically treated mixture was subjected to ammonia removal treatment to finally obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0028] Example 2 1) using argon gas at a temperature of 58° C. and a velocity of 122 meters per second as an exciting gas flow and 28% hydrochloric acid solution as a strong acid medium to perform a first acid spray on a nano-alumina powder having an average particle size of 24 nanometers, wherein the amount of the strong acid medium used is 11 milliliters per gram of the nano-alumina powder, and the nano-alumina powder is further subjected to a second acid spray with the strong acid primary waste liquid generated during the acid spraying process, wherein the amount of the strong acid primary waste liquid used is increased to 36 milliliters per gram of the nano-alumina powder, and the strong acid secondary waste liquid generated during the acid spraying process is directly introduced into 15% sodium hydroxide for dissolution and recovery; washing the nano-alumina powder after the two acid spraying treatments with deionized water for 5 times, and drying the nano-alumina powder at a temperature of 75° C. for 45 minutes after washing to obtain a basic alumina intermediate; 2) Using automatic grinding technology, the basic alumina intermediate and 18 nanometer silica powder were mixed in a mass ratio of 75:25. During the grinding process, the spindle speed was 42 rpm, the pressure at the end of the grinding rod was 5100 Pa, and the grinding time was 21 minutes. The ground mixed powder was then placed in a 23% ammonia solution and sealed for ultrasonic treatment. The amount of ammonia solution was 3 ml per gram of mixed powder, the ultrasonic frequency was 90KHZ, the temperature was 60°C, and the ultrasonic treatment was carried out for 36 minutes. The ultrasonically treated mixture was placed in a heating and stirring device, the temperature was controlled at 72°C, and stirring was continued for 80 minutes. The ultrasonically treated mixture was subjected to ammonia removal treatment to finally obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0029] Example 3 1) using argon gas at a temperature of 48° C. and a velocity of 112 meters per second as an exciting gas flow and 30% hydrochloric acid solution as a strong acid medium to perform a first acid spray on a nano-alumina powder having an average particle size of 18 nanometers, wherein the amount of the strong acid medium used is 9 milliliters per gram of the nano-alumina powder, and the nano-alumina powder is further subjected to a second acid spray with the strong acid primary waste liquid generated during the acid spraying process, wherein the amount of the strong acid primary waste liquid used is increased to 26 milliliters per gram of the nano-alumina powder, and the strong acid secondary waste liquid generated during the acid spraying process is directly introduced into 18% sodium hydroxide for dissolution and recovery; washing the nano-alumina powder after the two acid spraying treatments with deionized water for 4 times, and drying it in an environment at a temperature of 65° C. for 40 minutes after washing to obtain a basic alumina intermediate; 2) Using automatic grinding technology, the basic alumina intermediate and 15 nanometer silica powder were mixed in a mass ratio of 70:30. During the grinding process, the spindle speed was 38 rpm, the pressure at the end of the grinding rod was 4800 Pa, and the grinding time was 19 minutes. The ground mixed powder was then placed in a 21% ammonia solution and sealed for ultrasonic treatment. The amount of ammonia solution was 4 ml per gram of mixed powder, the ultrasonic frequency was 80KHZ, the temperature was 56°C, and the ultrasonic treatment was carried out for 33 minutes. The ultrasonically treated mixture was placed in a heating and stirring device, the temperature was controlled at 65°C, and stirring was continued for 74 minutes. The ultrasonically treated mixture was subjected to ammonia removal treatment to finally obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0030] Example 4 1) using argon gas at a temperature of 53° C. and a velocity of 116 m / s as an exciting gas flow and 32% hydrochloric acid solution as a strong acid medium to perform a first acid spray on a nano-alumina powder having an average particle size of 22 nm, wherein the amount of the strong acid medium used is 10 ml per gram of the nano-alumina powder, and the nano-alumina powder is further subjected to a second acid spray using the strong acid primary waste liquid generated during the acid spraying process, wherein the amount of the strong acid primary waste liquid used is increased to 33 ml per gram of the nano-alumina powder, and the strong acid secondary waste liquid generated during the acid spraying process is directly introduced into 18% sodium hydroxide for dissolution and recovery; washing the nano-alumina powder after the two acid spraying treatments with deionized water for 5 times, and drying the nano-alumina powder in an environment at a temperature of 75° C. for 45 minutes after washing to obtain a basic alumina intermediate; 2) Using automatic grinding technology, the basic alumina intermediate and 17 nanometer silica powder were mixed in a mass ratio of 73:27. During the grinding process, the spindle speed was 40 rpm, the pressure at the end of the grinding rod was 4900 Pa, and the grinding time was 20 minutes. The ground mixed powder was then placed in a 21% ammonia solution and sealed for ultrasonic treatment. The amount of ammonia solution was 5 ml per gram of mixed powder, the ultrasonic frequency was 90KHZ, the temperature was 60°C, and the ultrasonic treatment was carried out for 34 minutes. The ultrasonically treated mixture was placed in a heating and stirring device, the temperature was controlled at 72°C, and stirring was continued for 70 minutes. The ultrasonically treated mixture was subjected to ammonia removal treatment to finally obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

[0031] The characteristic parameters of the photocurable 3D printing ceramic slurry prepared in Examples 1 to 4 are shown in Table 1: Table 1

[0032] It can be concluded from the above table that the ceramic phase volume ratio of the ceramic slurry prepared by the present invention is greater than or equal to 74%, the average particle size of the ceramic phase is less than or equal to 37 nanometers, the porosity of the photocurable 3D printed ceramic body is less than or equal to 8%, and the sintering shrinkage rate of the body is less than or equal to 5.3%.

[0033] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0034] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.

Claims

1. A method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage, characterized in that: include: The nano-alumina powder is treated by spraying acid, then washed and dried to obtain a basic alumina intermediate; The basic alumina intermediate is mixed with nano-silica powder to obtain a mixed powder, the mixed powder is placed in an ammonia solution and sealed for ultrasonic treatment, and finally an ammonia removal treatment is performed to obtain a light-cured 3D printing ceramic slurry with low sintering shrinkage.

2. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The average particle size of the nano alumina powder is 15-24 nanometers.

3. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The acid spraying treatment is specifically: During the acid spraying process, argon gas with a temperature of 46-58°C and a velocity of 105-122 m / s is used as the exciting gas flow, 28-32% hydrochloric acid solution is used as the strong acid medium, and the dosage of the strong acid medium is 8-11 ml per gram of nano-alumina powder; The nano-alumina powder is sprayed with strong acid medium for the first time, and the strong acid primary waste liquid generated in the acid spraying process is further sprayed with strong acid for the second time on the nano-alumina powder. The amount of the strong acid primary waste liquid is 22-36 ml per gram of nano-alumina powder. The strong acid secondary waste liquid generated in the acid spraying process is directly introduced into 15-20% sodium hydroxide for dissolution and recovery.

4. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The nano-alumina powder is subjected to acid spraying treatment, followed by washing and drying, and specifically: The washing process uses deionized water as a medium, washing 3 to 5 times, and the drying process is performed at a temperature of 60 to 75° C. for 35 to 45 minutes.

5. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The mass ratio of the basic alumina intermediate to the nano-silicon dioxide powder is 67-75:25-33.

6. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The average particle size of the nano silicon dioxide powder is 12 to 18 nanometers.

7. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The basic alumina intermediate and the nano-silicon dioxide powder are mixed by grinding to obtain a mixed powder, specifically: During the grinding process, the spindle speed is 36 to 42 revolutions per minute, the pressure at the end of the grinding rod is 4500 to 5100 Pa, and the grinding time is 17 to 21 minutes.

8. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The mixed powder is placed in an ammonia solution and sealed for ultrasonic treatment, specifically: The mixed powder is ultrasonically treated in a 19-23% ammonia solution, the amount of ammonia solution is 3-6 ml per gram of mixed powder, the ultrasonic frequency is 70-90 KHZ, the temperature is 52-60°C, and the ultrasonic treatment time is 30-36 minutes.

9. The method for preparing a photocurable 3D printing ceramic slurry with low sintering shrinkage according to claim 1, characterized in that: The ammonia removal treatment is specifically: The mixture after ultrasonic treatment was placed in a heating and stirring device, the temperature was controlled at 62-72° C., and stirring was continued for 70-80 minutes to remove ammonia from the mixture after ultrasonic treatment.

10. The photocurable 3D printing ceramic slurry with low sintering shrinkage prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The volume ratio of the ceramic phase of the prepared ceramic slurry is greater than or equal to 74%, the average particle size of the ceramic phase is less than or equal to 37 nanometers, the porosity of the photocurable 3D printed ceramic body is less than or equal to 8%, and the sintering shrinkage rate of the body is less than or equal to 5.3%.